Analisis economico de los experimentos de PROMYF con frijol en postrera, Honduras 1976 - Alvarado, L; Sanders, J.H. (International Center for Tropical Agriculture, 1977)
In 1976 expt. were conducted on var. trials, fertilization, insecticides, and herbicides in order to identify new technology that could be introduced into small- and intermediate-scale bean production in Honduras. Factors of a complete technological package were also discarded to identify the most important restraints of production in several localities during the 2nd planting season of the yr (postrera). Results of economic analysis carried out indicate that it is necessary to fmd a new improved var. if good returns in income are to be obtained. The use of fertilizers and insecticides increased costs. It is recommended to work more in the area of preventive pest control if a drastic reduction in yields is to be avoided. (CIAT)